2015
DOI: 10.1021/acs.iecr.5b01074
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, Properties, and Supercooling Prevention of Phase Change Material n-Octadecane Microcapsules with Peppermint Fragrance Scent

Abstract: A new kind of phase change material n-octadecane microcapsules containing peppermint fragrance scent has been synthesized through the interfacial polymerization of isophorone diisocyanate (IPDI) and hexamethylenediamine (HMDA). The average size, morphology, and chemical components of the microcapsules were characterized by laser particle size analyzer, scanning electron microscope (SEM), and Fourier transform infrared (FTIR), respectively. The thermal characterizations of the microcapsules were studied by diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…The result showed that Mg 3 BTC 2 ‐ and Ca 3 BTC 2 are the best nucleating agents. Nano‐copper, graphite nanoparticles, expanded graphite, and multi‐walled carbon nanotubes can also serve as the nucleating agents for PCMs. Besides, researchers added nucleating agents into microencapsulated PCMs to decrease their supercooling.…”
Section: Introductionmentioning
confidence: 99%
“…The result showed that Mg 3 BTC 2 ‐ and Ca 3 BTC 2 are the best nucleating agents. Nano‐copper, graphite nanoparticles, expanded graphite, and multi‐walled carbon nanotubes can also serve as the nucleating agents for PCMs. Besides, researchers added nucleating agents into microencapsulated PCMs to decrease their supercooling.…”
Section: Introductionmentioning
confidence: 99%
“…According to the correlation between the phase‐change enthalpies and the content of n‐octadecane in the microcapsules, the yield of microcapsules ( η ) and the encapsulation efficiency ( E en ) which represented the fabrication efficiency and the loading of n‐octadecane within the microcapsules were also counted as follows: η=WmicroWocta+WRSF×100% Een=WmicroWocta×ΔHm,microΔHm,octa×100% where W micro , W octa, and W RSF represented the weight of the resultant microcapsules, n‐octadecane and RSF in the synthetic process, respectively, Δ H m,micro and Δ H m,octa denoted the fusion enthalpy of the encapsulated n‐octadecane in the microcapsules and the bulk n‐octadecane, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Supercooling will lead a longer thermal discharge time and casts significant effects on the overall thermal performance of PCM microcapsules [122]. To suppress this phenomenon, Wu et al added 1-tetradecanol and paraffin into the oil phase of n-octadecane@polyurea microcapsules as nucleation agents [123]. However, the supercooling degree further increased as 1-tetradecanol increased from 8.3 wt.% to 12.5 wt.%, and paraffin encapsulated into core materials was helpful for promoting the formation of triclinic crystal l in n-octadecane.…”
Section: Ermal Characterizationmentioning
confidence: 99%